Middle Meningeal Artery Embolization for Chronic Subdural Hematoma - Catapano, Joshua S.; Nguyen, Candice L.; Wakim, Andre A.; Albuquerque, Felipe C.; Ducruet, Andrew F. (Frontiers in Neurology, 2020)
Chronic subdural hematoma (cSDH) is a common disease process associated with significant morbidity that occurs most often in elderly patients. Asymptomatic patients are typically treated conservatively, with surgical intervention reserved for patients with symptomatic and/or large hematomas that cause brain compression. However, conservatively managed cSDH cases frequently progress, and surgical evacuation of cSDH is associated with high rates of complication and recurrence. Recently, successful treatment of cSDH via middle meningeal artery (MMA) embolization has been reported in small case series and case reports. This article reviews the existing literature on MMA embolization for cSDH and discusses the need for randomized control trials and/or large prospective studies to establish the efficacy of MMA embolization for this disease.